The effect of plyometric training on the explosive strength of leg muscles of volleyball players on single foot and two-foot takeoff jumps - Milic, V.; Nejic, D.; Kostic, R. (Facta Universitatis: Series Physical Education and Sport, 2008)
In order to determine the effects of plyometric training on the explosive strength of cadet volleyball players, we studied the effects of a six-week plyometric training program during the second half of the preliminary period of the annual training cycle. The sample consisted of 46 subjects aged 16 (? 6 months). The experimental group consisted of 23 volleyball players, with an average height of 186.35 +/- 8.52 and average weight of 70.57 +/- 8.98. The control group consisted of 23 high school students, with an average height of 177.35 +/- 4.80 and body weight of 68.91 +/- 6.48, who had not been exposed to the plyometric method as part of their physical education classes. The sample of measuring instruments consisted of eight tests of explosive leg strength: the two-foot takeoff block jump, the right foot takeoff block jump, the left foot takeoff block jump, the two-foot takeoff spike jump, the right foot takeoff spike jump, the left foot takeoff spike jump, the standing depth jump and the standing triple jump. Using a multivariate and univariate statistical method, we were able to determine a statistically significant difference in explosive strength in favor of the experimental group. We determined an increase in explosive strength for the two-foot and single foot takeoff jumps.